1996
DOI: 10.2307/3588143
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Learning: Context and Opportunities for Acquiring Academic English

Abstract: This article explores how the Learning Together form of cooperative learning influenced opportunities for acquiring academic English by L2 learners in a 6th-grade social studies classroom. Our findings present a complex picture. Cooperative learning gave L2 learners a wide range of opportunities to acquire academic English. They gave and received help with academic terms, difficult academic concepts, and para-academic knowledge. They were exposed to and produced lexical and conceptual explorations and homonymi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 31 publications
3
38
0
1
Order By: Relevance
“…By now a fairly solid body of literature has accumulated, including two edited volumes containing a rich selection of conceptual and research studies (Holt, 1993;Kessler, 1992), a number of journal articles (e.g., Bejarano, 1987;Chang & Smith, 1991;Jacob, Rottenberg, Patrick, & Wheeler, 1996;Milleret, 1992;Szostek, 1994), as well as some practical language teaching materials specifically developed for the purpose of CL (e.g., Coelho, Winer, & Olsen, 1989). In addition, in her well-known book on small group work, Cohen (1994) devotes a whole chapter to discussing the bilingual classroom, which includes foreign language classes.…”
mentioning
confidence: 99%
“…By now a fairly solid body of literature has accumulated, including two edited volumes containing a rich selection of conceptual and research studies (Holt, 1993;Kessler, 1992), a number of journal articles (e.g., Bejarano, 1987;Chang & Smith, 1991;Jacob, Rottenberg, Patrick, & Wheeler, 1996;Milleret, 1992;Szostek, 1994), as well as some practical language teaching materials specifically developed for the purpose of CL (e.g., Coelho, Winer, & Olsen, 1989). In addition, in her well-known book on small group work, Cohen (1994) devotes a whole chapter to discussing the bilingual classroom, which includes foreign language classes.…”
mentioning
confidence: 99%
“…The most frequent opportunity in their study involved L2 students giving or receiving help with decoding academic terms. Jacob et al's (1996) findings are supported by research in mainstream education. In his study of monolingual English-speaking students in the United Kingdom, Dowrick (1993) found that cooperative learning arrangements gave rise to 50% more low-order talk than high-order talk in a mathematics class.…”
Section: Issues Of Academic Language Developmentmentioning
confidence: 53%
“…Regarding students' L2 achievement gained through cooperative learning methods as reported in the studies reviewed above, one must ask the question: What type of language is acquired, academic or basic conversation? Jacob, Rottenberg, Patrick, and Wheeler's (1996) study is one of the few that explore L2 learners' acquisition of academic language in cooperative learning contexts. Their findings present a complex picture of the influence of the Learning Together method on opportunities for acquiring academic English in a grade 6 social studies class.…”
Section: Issues Of Academic Language Developmentmentioning
confidence: 99%
“…Third, the Cooperative Learning rationale requires teachers to assign students into different groups based on a various variables, such as their second language competence. Such individual difference might discomfort those students who have not yet mastered the second language, and thus, impede their collaboration with more capable students (Jacob, Rottenberg, Patrick & Wheeler, 1996). Jolliffe.…”
Section: Theory Conceptual Framework and Current Debates On Stadmentioning
confidence: 99%